Data set on Rapid Diagnostic Tests (RDTs) and microscopy for diagnosing plasmodium falciparum and plasmodium vivax - Grace I. Olasehinde; Uche C. Oyeka; Margaret I. Oniha; Olabode A. Onile-ere; Olayemi O. Ayepola; Adesola A. Ajayi; Louis O. Egwari (Data in Brief, 2018)
The World Heal Organization (WHO) has identified malaria diagnosis as being pivotal to eradicating the disease by 2030 as stipulated in the Sustainable Development Goals (SDG). The data presented here was obtained from outpatients of a hospital in the South Western Region of Nigeria from November 2016 to May 2017. The data contains malaria incidence amongst asymptomatic and symptomatic outpatients in the period under review. Malaria incidence was obtained using two diagnostic test kits, Bioline SD (HRP-2) and ACON (HRP-2/Aldolase) alongside Microscopy as gold standard. Specificity, Sensitivity and Kappa statistic of each test device is presented in the tables herewith. Data presented here could be used alongside other data sources to assess the state of malaria diagnostics.